2022
DOI: 10.1177/17589983221083994
|View full text |Cite
|
Sign up to set email alerts
|

Mobilisation or immobilisation-based treatments for first carpometacarpal joint osteoarthritis: A systematic review and meta-analysis with subgroup analyses

Abstract: Introduction Both joint mobilisation and immobilisation are thought to be effective in the treatment of first carpometacarpal joint (CMCJ) osteoarthritis (OA). The objective of this review was to establish whether either intervention reduced pain and improved pinch strength in people with first CMCJ OA in the short term and assess whether one intervention is superior to the other. Method This was a systematic review and meta-analysis. Seven databases were searched until May 2021. Only RCTs were included. The C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 51 publications
1
1
0
Order By: Relevance
“…Con-sidering the objectives of the present review, a direct overall comparison between our results with the systematic reviews that do not contain an active component is difficult. Nevertheless, our findings are in agreement with two previous systematic reviews and meta-analyses that suggested low and very low certainty of evidence for the superiority of unimodal or multimodal physiotherapy interventions including exercises in thumb CMCJ OA in pain and function in the short term [5,41]. However, the results of these reviews should be interpreted with caution because both studies included only three RCTs that evaluated the use of exercises in thumb CMCJ OA.…”
Section: Main Findings and Comparison With Other Reviewssupporting
confidence: 90%
“…Con-sidering the objectives of the present review, a direct overall comparison between our results with the systematic reviews that do not contain an active component is difficult. Nevertheless, our findings are in agreement with two previous systematic reviews and meta-analyses that suggested low and very low certainty of evidence for the superiority of unimodal or multimodal physiotherapy interventions including exercises in thumb CMCJ OA in pain and function in the short term [5,41]. However, the results of these reviews should be interpreted with caution because both studies included only three RCTs that evaluated the use of exercises in thumb CMCJ OA.…”
Section: Main Findings and Comparison With Other Reviewssupporting
confidence: 90%
“…be interpreted with caution because functional outcomes were not included. 26 Another systematic review has advocated the superiority of unimodal or multimodal physiotherapy interventions including exercises in CMC OA; however, their literature search was conducted seven years ago and several recently published studies have not been considered. 6 Also, comparisons between physiotherapy with or without exercises against different types of injections remains inconclusive.…”
Section: Data Analysis Synthesis and Summary Of Findingsmentioning
confidence: 99%